2014
DOI: 10.1364/ol.39.001402
|View full text |Cite
|
Sign up to set email alerts
|

Experimental demonstration of optical data links using a hybrid CAP/QAM modulation scheme

Abstract: The first known experimental demonstrations of a 10  Gb/s hybrid CAP-2/QAM-2 and a 20  Gb/s hybrid CAP-4/QAM-4 transmitter/receiver-based optical data link are performed. Successful transmission over 4.3 km of standard single-mode fiber (SMF) is achieved, with a link power penalty ∼0.4  dBo for CAP-2/QAM-2 and ∼1.5  dBo for CAP-4/QAM-4 at BER=10(-9).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…The plots indicate that small timing offsets can lead to significant performance degradation, with the effect becoming more severe for higher constellation orders. Ways to mitigate this issue include the use of appropriate algorithms to optimize the decision at receiver [78,79], the use of modified pulse shapes which exhibit better tolerance to timing jitter [80,81], the use of a modified QAM receiver instead of the conventional CAP receiver [82,83], or the use of an additional synchronization circuit at the receiver to perform both bit and frame synchronization [84]. Additionally, it has also been shown that the use of a fractional-space equalizer instead of a single-space equalizer at the receiver can provide enhanced insensitivity to timing jitter [85].…”
Section: Carrierless Amplitude and Phase Modulationmentioning
confidence: 99%
“…The plots indicate that small timing offsets can lead to significant performance degradation, with the effect becoming more severe for higher constellation orders. Ways to mitigate this issue include the use of appropriate algorithms to optimize the decision at receiver [78,79], the use of modified pulse shapes which exhibit better tolerance to timing jitter [80,81], the use of a modified QAM receiver instead of the conventional CAP receiver [82,83], or the use of an additional synchronization circuit at the receiver to perform both bit and frame synchronization [84]. Additionally, it has also been shown that the use of a fractional-space equalizer instead of a single-space equalizer at the receiver can provide enhanced insensitivity to timing jitter [85].…”
Section: Carrierless Amplitude and Phase Modulationmentioning
confidence: 99%
“…3 that the DAC/ADCs consume substantial power. Analogue implementations can be adopted for PAM-4 and hybrid CAP/QAM without the need of DAC/ADCs and thus can further improve power efficiency [12]. Alternatively, photonic integration can improve system power efficiency.…”
Section: Pam-4 Encodermentioning
confidence: 99%
“…For hybrid CAP-16/QAM-16, it generates a QAM like signal by combining two multi-level signals using two electrical filters whose impulse responses form an orthogonal Hilbert pair [10]. At the receiver, a modified QAM receiver is used to eliminate the crosstalk between I and Q channels that a CAP receiver otherwise has [11,12]. Such a hybrid CAP/QAM system offers not only improved tolerance to timing jitter but also increased system power margin compared with a conventional CAP receiver [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore desirable to propose an alternative approach with simple implementations. We have recently shown that single band hybrid CAP/quadrature amplitude modulation (QAM) transmitter/receiver scheme instead of a conventional non phase compensated CAP transceiver [14] can significantly improve not only the system jitter tolerance but also optical link power margin. In this work, for the first time, we propose and theoretically investigate hybrid multiband (HMB) CAP/QAM systems to tackle the practical timing jitter issue that have not received enough attention in previous work [7,12,13].…”
Section: Introductionmentioning
confidence: 99%